Swann song: antibiotic regulation in British livestock production (1953–2006) - Kirchhelle, C (Bulletin of the History of Medicine, 2018)
Antibiotics have played a significant yet ambivalent role in Western livestock husbandry. Mass introduced to agriculture to boost animal production and reduce feed consumption in the early 1950s, agricultural antibiotics were soon accused of selecting for bacterial resistance, causing residues and enabling bad animal welfare. The dilemma posed by agricultural antibiotic regulation persists to this day. This essay traces the history of British antibiotic regulation from 1953 to the influential 1969 Swann report. It highlights the role that individual experts using bacteriophage typing played in warning about the mass selection for bacterial resistance on farms and the response of a corporatist system, whose traditional laissez-faire arrangements struggled to cope with the risk posed by bacterial resistance. In addition to contextualizing the Swann report’s origins, the essay also discusses the report’s fate and implications for current antibiotic regulation.